2005
DOI: 10.1111/j.1365-313x.2005.02346.x
|View full text |Cite
|
Sign up to set email alerts
|

Senescence‐associated vacuoles with intense proteolytic activity develop in leaves of Arabidopsis and soybean

Abstract: SummaryVacuolar compartments associated with leaf senescence and the subcellular localization of the senescencespecific cysteine-protease SAG12 (senescence-associated gene 12) were studied using specific fluorescent markers, the expression of reporter genes, and the analysis of high-pressure frozen/freeze-substituted samples. Senescence-associated vacuoles (SAVs) with intense proteolytic activity develop in the peripheral cytoplasm of mesophyll and guard cells in Arabidopsis and soybean. The vacuolar identity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
307
0
47

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(368 citation statements)
references
References 61 publications
14
307
0
47
Order By: Relevance
“…Indeed, in situ hybridization analysis indicated that members of this family are specifically transcribed in cells where bacteroids are degraded (W. Van de Velde and S. Goormachtig, unpublished data). As an analogy, SAG12-green fluorescent protein fusions have recently been observed in senescence-associated vacuoles that are only present in chloroplast-containing leaf cells that undergo senescence (Otegui et al, 2005). Whether these SAG12 Cys protease-containing vesicles are involved in degradation of chloroplast proteins is currently unknown.…”
Section: Nodule Versus Leaf Senescencementioning
confidence: 99%
“…Indeed, in situ hybridization analysis indicated that members of this family are specifically transcribed in cells where bacteroids are degraded (W. Van de Velde and S. Goormachtig, unpublished data). As an analogy, SAG12-green fluorescent protein fusions have recently been observed in senescence-associated vacuoles that are only present in chloroplast-containing leaf cells that undergo senescence (Otegui et al, 2005). Whether these SAG12 Cys protease-containing vesicles are involved in degradation of chloroplast proteins is currently unknown.…”
Section: Nodule Versus Leaf Senescencementioning
confidence: 99%
“…fab1 plants kept at 2°C for up to 5 weeks are able to recover and set seed after a return to 22°C (Wu et al, 1997). We originally suggested that this chloroplast degradation at low temperature was a form of autophagy; however, recent reports of vacuole formation and chloroplast degradation during natural or dark-induced senescence provide alternative models for the process that occurs following the collapse of photosynthesis in fab1 plants at 2°C (Otegui et al, 2005;Ishida et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…A senescence-associated formation of special vacuoles containing a senescence-specific cysteine protease has been detected in leaves of Arabidopsis and soybean (Otegui et al 2005). Ricinosomes (precursor protease vesicles) containing large amounts of a papain-type cysteine endopeptidase develop at the beginning of programmed cell death in the nucellus of Ricinus communis Greenwood et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of endopeptidases and carboxypeptidases are localized in vacuoles (Brouquisse et al 2001;Huffaker 1990;Otegui et al 2005). Recently, the possibility has been discussed that vacuolar proteases are involved in the degradation of plastidial proteins during senescence of purple nutsedge (Fischer et al 1998).…”
Section: Introductionmentioning
confidence: 99%